UPLIFT-RELATED HYDROCARBON ACCUMULATIONS: THE RELEASE OF NATURAL GAS FROM GROUNDWATER - Cramer B.; Schlömer S.; Poelchau H.S. (My University, 2002)
Vertical tectonic movements often change the structural style and physico-chemical habitat of sedimentary basins. Changes in pressure, temperature and salinity of the groundwater caused by tectonic uplift may result in the release of previously dissolved gas. This process of gas exsolution from groundwater is shown to be an important mechanism in the formation of gas accumulations in uplifted basins. Two principal types of gas release are discussed. A hydrodynamic type is active when groundwater flows into areas of lower pressure or mixes with water of different temperature or salinity. It is anticipated that this effect is more of local importance, but over long periods of groundwater flow large volumes of gas may be exsolved. The hydrostatic type of gas release can occur in any sequence of sedimentary rocks where uplift causes a drop in pressure and temperature. This phenomenon may act basin-wide. Mass balance calculations show that the largest gas accumulations on Earth, such as the Urengoy field in West Siberia, could have been formed by this process.